Inquérito soroepidemiológico sobre Chikungunya, Dengue e Zika no município de Quixadá, Ceará - Braga, Dayse Aparecida de Oliveira (2020)
Arboviruses are a public health problem in the world and research that seeks to identify factors associated with their occurrence contributes to a better understanding of their transmission and can assist in the conduct of specific interventions. This study aimed to analyze the seroprevalence of dengue/Zika and chikungunya, and their possible associated factors, in the city of Quixadá, Ceará, Brazil, as well as to identify the spatial distribution patterns of positive cases. A cross-sectional survey was carried out from June 2018 to December 2019 in the city of Quixadá, Ceará, Brazil. To start the study, residences were selected and all residents were invited to participate in the research through the application of a questionnaire and the collection of 10ml of blood. The samples were transported to the Laboratório Central de Saúde Pública do Ceará in Fortaleza, Ceará, Brazil, where they were analyzed by the ELISA serological test. The data were entered into the EpiInfo 7.2 software and the analysis performed in the Stata 15.1 software. The spatial analysis of the cases was carried out through the Kernel density, using the Arcgis 9.2 program. 409 samples were analyzed, of which 70.7% (n=289) were seropositive for previous exposure to CHIKV and 97.8% (n=400) to previous exposure to DENV/ZIKV. Bigger seropositivity for DENV/ZIKV was observed in females (98.5%). The most frequent symptom was joint pain (274; 68.5%). There were reports of 240 (58.7%) of having already had chikungunya and 281 (68.7%) reported some arbovirus (dengue, chikungunya or Zika). The most frequent symptom was joint pain (242; 83.7%). Two areas of high density of dengue/Zika cases and one of medium density were found in the central region of the city. Greater seropositivity for CHIKV was found in female participants (75.5% - 206-273), aged 31 to 60 years (75.0% - 162/216), in those with monthly family income less than one salary minimum (89.5% - 34/38), in housewives (87.5% - 56/64), and in those with schooling up to elementary school (75.0% - 99/132). The female sex presented a higher seroprevalence of CHIKV (PR = 1.23; 95% CI: 1.06-1.43; p = 0.003), as well as morning stiffness (PR = 1.24; 95% CI: 1.09- 1.43; p <0.001). After adjusting for age groups with Poisson's hierarchical regression, the only variable that remained associated was morning stiffness (PR = 1.20; 95% CI: 1.06–1.37; p <0.001). An area of high density of cases of chikungunya and two areas of medium density were observed, in the central region of the municipality, close to each other. The study data show a hyperendemicity of arboviruses in Quixadá, indicating that there was a continuous and comprehensive circulation of the dengue / zika and chikungunya viruses in the city. The higher prevalence of dengue is due to a longer exposure time of the population, however, even with only one epidemic wave, there was already a high prevalence of cases of chikungunya.